Strategi Komunikasi Humas Dinas Lingkungan Hidup Provinsi Jawa Barat dalam Kampanye Pengurangan Plastik Sekali Pakai - Dira Novianti; Amy Elva Silviany (CV. ITTC INDONESIA, 2026)
The West Java Provincial Environmental Agency (DLH) Public Relations' communication strategy in its campaign to reduce the use of single-use plastics is motivated by the high use of plastics that impact environmental problems. The West Java DLH Public Relations acts as a liaison between government policies and the public through the delivery of persuasive and educational messages to encourage behavioral change in the campaign for the use of single-use plastics. The purpose of this study is to determine how the West Java DLH Public Relations' communication strategy is implemented, the messages and media used, and its impact on public awareness. This study uses a qualitative approach with descriptive methods. Data collection techniques are carried out through observation, interviews, and documentation. The results show that the West Java DLH Public Relations' communication strategy is implemented through environmental campaigns, socialization, and publication of the single-use plastic reduction program by utilizing social media, websites, and direct educational activities. These communication efforts are able to increase public awareness and participation in the issue of reducing single-use plastics, although still facing difficulties in changing people's habits. Therefore, a consistent and sustainable communication strategy is an important factor in supporting the success of reducing the use of single-use plastics in West Java.